Evaluación del desempeño de dos ácidos grasos obtenidos a partir del aceite esencial de naranja y aceite vegetal de aguacate en la formulación de un fluido sintético a nivel de laboratorio (2021)
Oil-based drilling fluids present numerous advantages in the control of properties in drilling operations, generally the continuous phase used in these systems is diesel or mineral oils, which have a high environmental impact, because they contain 22% of aromatic compounds. For this reason, the main objective of this research project is to evaluate the performance of two fatty acids obtained from orange essential oil and avocado vegetable oil in the formulation of an inverse emulsion-synthetic oil-based drilling fluid at laboratory level, being this an alternative with less environmental impact and a contribution to the development of new technologies in drilling fluids, without affecting their functionality with respect to conventional drilling fluids.